2019
DOI: 10.1155/2019/7403978
|View full text |Cite
|
Sign up to set email alerts
|

Tangduqing Granules Attenuate Insulin Resistance and Abnormal Lipid Metabolism through the Coordinated Regulation of PPARγ and DGAT2 in Type 2 Diabetic Rats

Abstract: Insulin resistance (IR) is a vital hallmark of type 2 diabetes mellitus, which is characterized by an impaired ability of insulin to promote glucose uptake and utilization. Lipid deposition is closely associated with impaired insulin sensitivity. PPARγ plays an important role in glucose homeostasis, adipocyte differentiation, and insulin sensitivity. Likewise, DGAT2 also exerts a crucial role in integrating carbohydrate and lipid metabolism in the liver. The present study is aimed at evaluating a Chinese medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Therefore, in this study, the PA-induced HepG2 cells hepatosteatosis model was utilized for evaluating the lipid-lowering ability of PPYP. Consistent with previous studies [48], our study showed that PA could significantly increase lipid accumulation in a dose-dependent manner in HepG2 cells. PPYP significantly reduced TG content, indicating the inhibition of the PA-induced steatosis in HepG2 cells.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, in this study, the PA-induced HepG2 cells hepatosteatosis model was utilized for evaluating the lipid-lowering ability of PPYP. Consistent with previous studies [48], our study showed that PA could significantly increase lipid accumulation in a dose-dependent manner in HepG2 cells. PPYP significantly reduced TG content, indicating the inhibition of the PA-induced steatosis in HepG2 cells.…”
Section: Discussionsupporting
confidence: 93%
“…The dissociation in this model was strongly confirmed by down-regulation of DGAT2. Because in previous studies, they found overexpression of DGAT2 can cause hepatic insulin resistance in mice models of severe hepatic steatosis (37,38). Moreover, in insulin resistance obesity, the study also found that mice with deletion of X-box-binding protein-1(XBP-1) can lead to develop insulin resistance in HFD-dieted conditions (39), and the other study further found that the upregulation of IκB kinase beta (IKKβ) activity in the liver of obese mice can increase XBP1s activity and reduce ER stress, resulting in a significant improvement in insulin sensitivity (40).…”
Section: Discussionmentioning
confidence: 94%
“…DGAT2 overexpression in the liver of mice increases hepatic TG content, leading to NAFLD and hepatic insulin resistance (Jornayvaz et al, 2011). An early study reported that Tangduqing granules decrease DGAT2 expression, resulting in a relief of insulin resistance and hypertriglyceridemia in a T2DM rat model (Zhang et al, 2019). A previous study has demonstrated that metformin could reduce DGAT2 expression and hepatic lipid biosynthesis in diabetic mice, but the underlying molecular mechanism was unclear (Choi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Mice with hepatic overexpression of DGAT2T exhibit profound hepatic insulin resistance and steatosis (Jornayvaz et al, 2011). Inhibition of DGAT2 expression has been shown to improve insulin resistance and hepatic steatosis in T2DM rats, suggesting that DGAT2 plays an important role in hepatic steatosis and hypertriglyceridemia in T2DM (Choi et al, 2007;Zhang et al, 2019). X-box binding protein 1 (XBP1) functions as a transcription factor in response to endoplasmic reticulum (ER) stress, adipocyte differentiation, and fatty acid and TG synthesis, with DGAT2 serving as a downstream target gene of XBP1 (Yoshida et al, 2001;Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%